Plant pathogens : detection and management for sustainable agriculture - Kumar, Pradeep (Professor of biotechnology); Tiwari, A. K. (Ajay K.); Kamle, Madhu; Abbas, Zafar (Professor of botany); Singh, Priyanka, 1975- (Burlington, ON, Canada ; Palm Bay, Florida : Apple Academic Press Inc., 2020)
"Plant Pathogens: Detection and Management for Sustainable Agriculture addresses the most critical issues in the management of emerging diseases throughout the world. Experts in plant pathology from internationally renowned institutes share their research and examine key literature on vital issues in pathogen disease diagnosis and management. They look at both traditional pathology as well as new and advanced biotechnological and molecular diagnosis approaches. This book is divided into four parts, covering viral and fungal disease detection and management, nematode diseases and management, bio-control, and biotechnological approaches and impact of climate change. The authors look at the challenges of crop protection against diseases caused by plant pathogens for the most economically important crops, including fruits, vegetables, and cereals. The establishment and management of plant diseases using conventional and eco-friendly methods are discussed with an emphasis on the use of beneficial microbes and modern biotechnological approaches. Plant Pathogens: Detection and Management for Sustainable Agriculture focuses on expert disease diagnosis and integrated management practices with molecular diagnostic techniques to achieve disease free-plants from a wide array of pathogens. The volume will be a valuable source of information for those involved with and studying plant pathology and crop disease management"--
Viral Diseases of Okra in Ghana and Their Management / Elvis Asare-Bediako -- Current and Prospective Approaches for Plant Virus Diseases Detection / Touseef Hussain1, and Quazi Mohd. Imranul Haq -- Virus Afflictions of Anticancerous Medicinal Plant Catharanthus roseus (L.) G.Don / Deepa Srivastava and K. Shukla -- Important Diseases of Papaya and Their Integrated Disease Management / Diganggana Talukdar, Utpal Dey, and G. P. Jagtap -- Fungal Diversity under Different Agri-Systems and Their Beneficial Utilization in Plant Health Management / Vibha -- Mycoflora Associated with Paddy Varieties / Shveta Malhotra -- Plant Disease Detection and Management: An Overview / S. M. Yahaya -- Role of Biological Agents for the Management of Plant Parasitic Nematodes / Aamir Raina, Mohammad Danish, Samiullah Khan, and Hisamuddin -- Principles and Concepts of Integrated Nematode Management in Major Crops / B. S. Sunanda and Ravulapenta Sathish -- Lichens: A Novel Group of Natural Biopesticidal Sources / Vinayaka S. Kanivebagilu and Archana R. Mesta -- Antimicrobial Peptides from Biocontrol Agents: Future Wave in Plant Disease Management / Vivek Sharma and Richa Salwan -- Plant Disease Management Using Biotechnology: RNA Interference / Naresh Pratap Singh and Vaishali -- Engineering Plastid Pathways: An Environment-Friendly Alternative for in Planta Transformation / Bhavin S. Bhatt and Achuit K. Singh -- Impact of Meteorological Variables and Climate Change on Plant Diseases / A. K. Misra, S. B. Yadav, S. K. Mishra, and M. K. Tripathi.
OCLC-licensed vendor bibliographic record.
Keywords: Phytopathogenic microorganisms -- Research; TECHNOLOGY / Agriculture / General